2005
DOI: 10.1038/nrc1613
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy and chemotherapy — a practical partnership

Abstract: This article discusses how recent data have altered the way we understand how dying tumour cells, particularly those killed by chemotherapy, engage with antitumour immune responses. These data have significant implications for the development of new protocols combining chemotherapy with immunotherapy, indicating an exciting potential for therapeutic synergy with general applicability to many cancer types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
397
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 600 publications
(409 citation statements)
references
References 62 publications
10
397
1
1
Order By: Relevance
“…For example, some anticancer drugs increase the expression of death receptors, including FAS, TNF receptors and TNF-related apoptosis-inducing ligand receptors. 94 Other drugs trigger apoptosis by inducing release of cytochrome c from mitochondria. 94 The degree of TCD correlates with clinical outcome in several tumor settings.…”
Section: Effects On Tumor Cells and On Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some anticancer drugs increase the expression of death receptors, including FAS, TNF receptors and TNF-related apoptosis-inducing ligand receptors. 94 Other drugs trigger apoptosis by inducing release of cytochrome c from mitochondria. 94 The degree of TCD correlates with clinical outcome in several tumor settings.…”
Section: Effects On Tumor Cells and On Tumor Microenvironmentmentioning
confidence: 99%
“…94 Other drugs trigger apoptosis by inducing release of cytochrome c from mitochondria. 94 The degree of TCD correlates with clinical outcome in several tumor settings. 95,96 Some chemotherapeutics, including anthracyclines, oxaliplatin and CTX, are unique in their capacity to induce an immunogenic type of TCD, 21,97 thereby converting dying tumor cells into adjuvanted-endogenous vaccines.…”
Section: Effects On Tumor Cells and On Tumor Microenvironmentmentioning
confidence: 99%
“…Therefore, many efforts have been directed toward the development of immunotherapeutic approaches to enable the immune system to respond specifically against cancer. 20,89 Dendritic cells have different sensitivities to conventional cytotoxic agents. In this aspect, it was reported that PTX and other chemotherapeutic agents could up-regulate DC functions in vitro.…”
Section: Immunomodulatory Effects Of Ultra-low Concentrations Of Chemmentioning
confidence: 99%
“…Conversely, TLR-targeted therapy may enhance subsequent responses to chemotherapy. Such combinations have been explored in a number of preclinical studies, sometimes with promising results (Lake and Robinson, 2005;Bourquin et al, 2006;Shi et al, 2007). For example, Shi et al (2007) demonstrated enhanced chemo-sensitivity of chronic lymphocytic leukemia cells after tolerizing treatment with the TLR7 agonist, S28690.…”
Section: Tlr Ligands In Cancer Immunotherapymentioning
confidence: 99%